Boas práticas na atenção ao pré-parto, parto e puerpério na pandemia da COVID-19 na percepção de enfermeiras obstetras - Freitas, Cira Cardoso (2022)
The search for the perinatal healthcare quality based on good practices of healthcare on childbirth and on sexual and reproductive rights have been globally widespread in decades. However, with the COVID-19 pandemic scenario set up since the beginning of 2020, these rights, hardly achieved throughout years of progress, have been threatened. The requirement of quarantine to avoid the COVID-19 infection affected the perinatal care, with potential impact on labour, childbirth, and pospartum good practices, which are key to foster a positive childbirth experience. Aim: To investigate the impact of COVID-19 pandemic on delivery and post-delivery good practices, through the insight of obstetric nurses. Methodology: A qualitative, exploratory, and descriptive study from the conceptual perspective of good practices on the labour and childbirth care. It is part of the multicentric project “Inquérito Nascer COVID” [COVID Birth Inquiry], from the Universidade Federal do Triângulo Mineiro [Triângulo Mineiro Federal University], in partnership with the Universidade Federal de São Carlos [São Carlos Federal University]. The study population consisted of obstetric nurses contacted by the Inquérito Nascer Covid team, because they were registered on the social media of the extension project “@nascer.e. COVID” /“Nascer e COVID”, from Instagram® and Facebook. Results: From the 13 midwives interviewed, most of them declared themselves white, between 25-46 years of age with lato sensu post-graduation, currently working on delivery direct assistance and receiving an average of 7 minimum wages. The interview data came from 3 subject categories: “Changing in the labour, childbirth and postpartum healthcare practices”, “Presence of a birth companion”, and “Support network”. Considerations: Although some study participants have reported a decreased impact of COVID-19 pandemic on the delivery good practices, most of them raises the question for a retrogression timeframe regarding the women’s rights at the cost of hygienist measures and virus transmission control in the pandemic timeframe, which can probably impact the experience of women in delivering. It is also worth mentioning professionals who provide healthcare in an out-of-hospital setting highlighted a minimal impact on good practices, and they believe this is the cause of an increasing search of this service by families.